"A saving return" - the dramaturgy of a journey in time, space and language in the play Crimea by Małgorzata Trajkowska and Vera Popova - Zalewska, Alicja (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
The article presents the dramaturgic strategies in the play Crimea by the Sztuka Nowa Association. The creators – Vera Popova and Małgorzata Trajkowska – take viewers on a journey across and beyond borders, into distant times and the recent past, as well as through language barriers resulting not only from cultural differences, but also from the fundamental difficulty of translating emotional experience into words. Refraining from a political theater, the artists create a play, which deals with the subject of the recent annexation of Crimea by Russia. At the same time, as in the autotheatre Joanna Krakowska’s theory, they talk about their own, intimate experiences related to the trip to the Black Sea coastline. They present a journey that takes place not only in time and space, but also in emotions and experiences of their bodies. Fueled by the beauty in melancholy of Julia Kristeva's theory, the play is at the same time ironically distanced and grotesquely humorous. Numerous postdramatic solutions situate the performance in a historical, sociopolitical, personal, aesthetic and existential narrative at the same time. Physical theater, Popova's and Trajkowska's motherland, is related to body art and dance techniques. Therefore, their art might be analyzed with the Daniel Sibony's idea of dancing between two bodies: one remembering and one present, but also with Dorota Sajewska’s theory of the body as an archive.